ChemInform Abstract: Enantioselective Metal/Organo‐Catalyzed Aerobic Oxidative sp3 C—H Olefination of Tertiary Amines Using Molecular Oxygen as the Sole Oxidant. Issue 5 (13th February 2013) - Zhang, Gen; Ma, Yunxia; Wang, Shoulei; Zhang, Yaohu; Wang, Rui
Abstract N‐Aryltetrahydroisoquinolines are olefinated by acrylaldehyde, methyl or ethyl vinyl ketone, or acrylonitrile in the presence of a copper(II)/quinine catalyst system to give the corresponding 1‐alkenyltetrahydroisoquinolines (22 examples) with up to 99% enantioselectivity.